Grid-based Image Encryption using Code-based Cryptography - Bhagaskoro, Dian Anggoro Putro; Barmawi, Ari Moesriami (School of Computing, Telkom University, 2020)
Recently, image is frequently sent or exchanged electronically, such that image security is important. A method for securing images is using RSA. However, RSA needs more time for securing an image. For overcoming the RSA problem, McEliece Cryptosystem is introduced to grid-based image encryption. The image is divided into blocks and each block is divided into grids, then finally McEliece Cryptosystem is applied to the pixels in the grids. Based on the experimentâ€™s result, it was proven that the execution time of the proposed method is less than the previous one, while maintaining the security. Keywords: McEliece Cryptosystem, RSA, Image Encryption, Image Decryption, GridÂ